Material didáctico digital como apoyo al proceso de enseñanza-aprendizaje en la asignatura de ciencias naturales para estudiantes de 8vo año de EGB de la Unidad Educativa San Pedro - Bajaña Rivera, Anabelly Selena (2024)
The present research work had as a starting point the investigation of different opportune digital tools that allow us to develop digital teaching material based on the subject of Natural Sciences to implement as support in the teaching-learning process of the 8th year students of Basic General Education of the San Pedro de Guanujo Educational Unit of the city of Guaranda. For the research project, a mixed methodology was chosen where quantitative and qualitative aspects were combined in order to achieve a full understanding of the subject. The study focused on the sample of 47 students of the eighth year of Basic General Education of the San Pedro Educational Unit and was presented under a descriptive and transversal design. Among the methods used, the inductive - deductive, the bibliographic and the analytical - synthetic were incorporated. Data collection techniques such as observation were applied using a form as an instrument to identify the learning methods and strategies applied by the teacher in the classroom, surveys applied to the students through a questionnaire consisting of seven questions and finally interviews implemented with the teachers of the Natural Sciences area through a questionnaire consisting of five questions, obtaining data to be able to elaborate their respective analysis and interpretation and to be able to determine the importance or need that the students have to incorporate digital teaching material in their teaching process. It is concluded that with the implementation of digital teaching material as support to the teaching process in the Natural Sciences subject, it was possible to strengthen knowledge and stimulate interest in learning through technology, in this way being able to develop critical thinking and obtain better learning results.